Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1080/13693780500543246
|View full text |Cite
|
Sign up to set email alerts
|

Gangrenous necrosis of the diabetic foot caused byFusarium acutatum

Abstract: Foot infections are common and serious complications of diabetic patients. We report the case of a 68-year-old patient with a diabetic foot infection that developed into a gangrenous necrosis. Fusarium spp. was isolated on two successive occasions with no other associated microorganisms. Histopathology demonstrated invasion of the fungus into the tisssue. These findings suggested an infection rather than colonization. A detailed morphological study showed that the isolate was Fusarium acutatum, which was confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…The spectrum of microbial infection occurring in these diabetic foot infections has already been reported. While most of these studies have focused only on the bacteria, very few studies have reported the presence of filamentous fungi [5,6]. Sometimes, the presence of low pathogenic yeast has also been reported in some studies [2,7].…”
Section: Introductionmentioning
confidence: 96%
“…The spectrum of microbial infection occurring in these diabetic foot infections has already been reported. While most of these studies have focused only on the bacteria, very few studies have reported the presence of filamentous fungi [5,6]. Sometimes, the presence of low pathogenic yeast has also been reported in some studies [2,7].…”
Section: Introductionmentioning
confidence: 96%
“…White piedra is a clinical condition caused by Trichosporon species (1,2). The most distinctive feature of this mycosis is the production of white-brown nodules adhered to the hair shaft that may easily be detached, in contrast with black piedra nodules (3). Despite awareness of white piedra in the medical field since the 19th century (4), there is little knowledge about its mechanisms of infection in humans (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Based on an extensive literature review, Nucci and Anaissie (48) recently recorded 12 morphospecies associated with fusarial infections within the immunocompromised patient population. However, phylogenetic species recognition based on genealogical concordance of multilocus DNA sequence data (herein referred to as GCPSR) (79) has identified at least 69 clinically important Fusarium species (Table 1) (49,54,56,57,70,85). Phylogenetic species in these studies were recognized if they received Ն70% maximum parsimony (MP) bootstrap support (78) from the majority of the individual gene partitions and the combined data set and if their monophyly was not contradicted by analyses of any of the individual singlegene partitions.…”
mentioning
confidence: 99%